Systematic review: Annual incidence of ACL injury and surgery in various populations - Moses, B.; Orchard, J.; Orchard, J. (Research in Sports Medicine, 2012)
Accurate documentation of injury incidence is critical for study of injury risk factors and prevention. Comparisons of published incidences of anterior cruciate ligament (ACL) injuries and surgical reconstructions are difficult, however, because of the variations in units. Some studies report absolute time-based denominators (such as annual incidence or incidence per 100,000 person years), whereas others report exposure-based denominators (such as incidence per 1,000 player hours or athlete exposures). We converted exposure-based units into annual incidences to compare various studies. National population studies show annual incidence rates of up to 0.05% per person per year in Australia. Professional athletes in basketball, soccer, and the other football codes report an annual incidence of 0.15%-3.7% in studies with at least a moderate sample size. Annual ACL incidence in amateur sporting groups was generally higher than the entire population but lower than among professional athletes. Converting incidence rates to annual units allowed better comparisons to be made between population rates across different studies.